A study of English borrowing in Patani-Malay / Noorhayatee Benjasmith - Noorhayatee, Benjasmith (2016)

(untitled)
This dissertation is a study of language borrowing process of English in Patani-Malay. The objectives of this study are to examine the phonological, morphological, and semantic changes of English lexical items used in Patani-Malay in order to identify their types of borrowing; as well as to sort and allocate these English lexical items into their respective semantic fields. The corpus of English lexical items used in this study was collected from various Patani-Malay printed media written in Jawi, Roman, and Thai scripts. They were analysed based on the works of Haugen (1950), Heah (1989), and Haspelmath & Tadmor (2009). The findings reveal that the data can be classified into various borrowing types under three borrowing processes i.e. Importation, Substitution, and Native Creation. In terms of the classification of the data into semantic fields, the data occur most in the semantic field of Modern World. It is followed by the semantic fields of Social and Political Relations, and Cognition.